Titan's surface bearing strength: Contact force models for the Dragonfly rotorcraft lander. (May 2022) - Lorenz, Ralph D.
Abstract: The bearing strength of surface materials expected in the Dragonfly's area of operations on Titan is considered, in order to inform landing dynamics simulations and define the required skid or footpad area of landing gear. In the hard limit, solid ice surfaces are practically unyielding and touchdown kinetic energy must be absorbed by the legs and structure. The soft limit corresponds to airfall organic dust on Titan, and defines the required foot area. As in previous lunar, Mars and comet lander missions, the strength estimate for 'soft' granular material (here ​∼ ​9 ​kPa for contingencies, and ∼20 ​kPa for nominal operations) is derived from the Terzaghi soil mechanics formalism, taking Titan material properties and gravity into account. A friction coefficient range of 0.1–0.75 is indicated from the literature on polymers and ice. A novel surface specification needed for Dragonfly is an adhesion term which defines the additional thrust (beyond weight) needed to takeoff in the event of sticky or muddy terrain. Laboratory data on slurries of grains in organic liquids, and analogs from the food industry, support a value of 3 ​kPa. Specifications on previous missions, and the terrestrial experience with skis and skids on aircraft, are reviewed for context. Highlights: Reviews planetary surface strength models on previous planetary missions. Assesses laboratory data and terrestrial aircraft experience (e.g. snow). Develops Titan strength model using Terzaghi equations. Proposes surface adhesion value for 'sticky' surfaces.